The Influence of Product Quality, Service and Price on Consumer Purchasing Decisions at Aneka Frozen Food and Fruits Mandetek, North Makale - Tappi , Serlina; Pali , Elisabet; K. Wibisono , Lisa K. Wibisono (JURNAL EKBIS, 2025)
This research was conducted with the aim of showing the influence of product quality, service quality and price on purchase decisions. The method used in this study is a quantitative method. The data collection technique was carried out by distributing questionnaires, the analysis used was multiple linear regression. The population in this study is consumers buying various frozen food and fruits from Mandetek, North Makale and the sample used was 40 people. Sample selection using purposive sampling. The data collection stage uses quantitative analysis using statistical analysis, namely the data instrument test (validity and reliability test), the classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis test, Prasial test, simultaneous test and determination coefficient (R2). The results of this study show that (1) through the t-test of Product Quality has an effect of 0.746 but not significantly 0.460 on consumer purchase decisions at Aneka Frozen Food and Fruits Mandetek, North Makale, (2) Service has an effect of 2.218 and significantly 0.033 on consumer purchase decisions at Aneka Frozen Food and Fruits Mandetek, North Makale, (3) Price has an effect of 2.550 and a significant 0.015 effect on consumer purchase decisions at Aneka Frozen Food and Fruits Mandetek, North Makale (4)Product Quality, Service and Price have a combined effect on consumer purchasing decisions at Aneka Frozen food and Fruits Mandetek, North Makale.